The 2018 Global Research Expedition on Altitude Related Chronic Health (Global REACH) to Cerro de Pasco, Peru: an Experimental Overview. Issue 1 (6th May 2020) - Tymko, Michael M.; Hoiland, Ryan L.; Tremblay, Joshua C.; Stembridge, Mike; Dawkins, Tony G.; Coombs, Geoff B.; Patrician, Alexander; Howe, Connor A.; Gibbons, Travis D.; Moore, Jonathan P.; Simpson, Lydia L.; Steinback, Craig D.; et al.
Abstract : New Findings: What is the central question of this study? Herein, a methodological overview of our research team's (Global REACH) latest high altitude research expedition to Peru is provided. What is the main finding and its importance? The experimental objectives, expedition organization, measurements and key cohort data are discussed. The select data presented in this manuscript demonstrate the haematological differences between lowlanders and Andeans with and without excessive erythrocytosis. The data also demonstrate that exercise capacity was similar between study groups at high altitude. The forthcoming findings from our research expedition will contribute to our understanding of lowlander and indigenous highlander high altitude adaptation. Abstract: In 2016, the international research team Global Research Expedition on Altitude Related Chronic Health (Global REACH) was established and executed a high altitude research expedition to Nepal. The team consists of ∼45 students, principal investigators and physicians with the common objective of conducting experiments focused on high altitude adaptation in lowlanders and in highlanders with lifelong exposure to high altitude. In 2018, Global REACH travelled to Peru, where we performed a series of experiments in the Andean highlanders. The experimental objectives, organization and characteristics, and key cohort data from Global REACH's latest research expedition are outlined herein. Fifteen major studies are described that aimed to elucidate the physiological differences in high altitude acclimatization between lowlanders ( n = 30) and Andean‐born highlanders with ( n = 22) and without ( n = 45) excessive erythrocytosis. After baseline testing in Kelowna, BC, Canada (344 m), Global REACH travelled to Lima, Peru (∼80 m) and then ascended by automobile to Cerro de Pasco, Peru (∼4300 m), where experiments were conducted over 25 days. The core studies focused on elucidating the mechanism(s) governing cerebral and peripheral vascular function, cardiopulmonary regulation, exercise performance and autonomic control. Despite encountering serious logistical challenges, each of the proposed studies was completed at both sea level and high altitude, amounting to ∼780 study sessions and >3000 h of experimental testing. Participant demographics and data relating to acid–base balance and exercise capacity are presented. The collective findings will contribute to our understanding of how lowlanders and Andean highlanders have adapted under high altitude stress. Abstract :